Safety Results from OCAPI: A European Observational Cohort Study of Insulin Glulisine-treated Children Aged 6–12 Years with Type 1 Diabetes - Konstantinova, M.; Loizeau, V.; Pilorget, V.; Cali, A.; Danne, T. (Experimental and Clinical Endocrinology & Diabetes, 2014)
Objective: Data on the safety of insulin glulisine for type 1 diabetes are limited in paediatric populations. The European post-marketing Observational prospective Cohort study of children with type 1 diabetes treated with APIDRA® (OCAPI) study evaluated the safety of insulin glulisine in children aged 6–12 years in real-life clinical practice, with a particular focus on the 6–8 years age group.Research design and methods: OCAPI was an international, multicentre, observational, non-interventional, prospective cohort study, in which 94 participants with type 1 diabetes (6–8 years age group: n=31; 9–12 years age group: n=63) received insulin glulisine for 6 months under normal, local conditions. The primary objective was the incidence of severe hypoglycaemia in all participants.Results: Overall incidence of severe hypoglycaemia was 6.6 events per 100 persons/year (7.2 and 6.3 events per 100 persons/year in the 6–8 and 9–12 years age groups, respectively). 12 participants (all aged 9–12 years) experienced transient injection-site reactions. No systematic hypersensitivity reactions were reported. Only 1 participant (9–12 years age group) experienced a serious class-effect risk possibly related to insulin glulisine (severe hypoglycaemia requiring an Emergency Department visit). Glycated haemoglobin levels did not change markedly throughout the study, and were inversely proportional to the risk of hypoglycaemia.Conclusions: Insulin glulisine has a good safety profile in children with type 1 diabetes aged 6–12 years, with generally low rates of severe hypoglycaemia and few adverse reactions. These results are encouraging for its use in paediatric populations.
Keywords: diabetes mellitus; type 1; children; insulin glulisine; safety; hypoglycaemia